PENGARUH KEPERCAYAAN PELANGGAN TERHADAP NIAT PEMBELIAN GADGET DI SHOPEE INDONESIA - Maria Regina Picaully (Jurnal Manajemen Maranatha, 2018)
Along with the development of e-commerce in Indonesia, customers are increasingly fond of shopping online to meet their needs including the needs of gadget products. However, despite the many benefits of online shopping, online shopping also has many risks to be faced. Meanwhile, whether or not a person's desire to shop online depends on the amount of benefits he receives when shopping compared to the risks he or she may encounter. One factor that can affect customers in shopping for gadgets online is the trust of customers towards online sellers. This is due to the difficulty of building trust between customers and sellers because they can not meet face to face and the product being sold can not be seen or held in the real way. This research uses descriptive and correlational method. Technique of collecting data of this research is spreading of questionaire to sample of research. After getting the data from the research sample then do the validity and reliability test data. Data that is valid and reliable then processed to know the respondent's assessment of customer trust and purchase intentions. To know the influence of customer trust on purchasing intention done linear regression analysis and t test. After doing these tests then make conclusions and suggestions. From the results of research can be concluded that Shopee Indonesia’s customers trust to gadget products are less good so affecting the intention of purchasing gadget products in Shopee Indonesia is not good . Keywords: word of mouth, customer trust, purchase intention